To analyze the recursive definition given for the sequence:
- The base term \( a_1 = 6 \).
- The recursive formula \( a_n = a_{n-1} + 2 \).
This indicates that each term in the sequence is generated by taking the previous term and adding 2.
Let's calculate the first few terms of the sequence:
- \( a_1 = 6 \)
- \( a_2 = a_1 + 2 = 6 + 2 = 8 \)
- \( a_3 = a_2 + 2 = 8 + 2 = 10 \)
- \( a_4 = a_3 + 2 = 10 + 2 = 12 \)
- \( a_5 = a_4 + 2 = 12 + 2 = 14 \)
- \( a_6 = a_5 + 2 = 14 + 2 = 16 \)
The sequence so far is \( 6, 8, 10, 12, 14, 16, \ldots \).
Now let's look at the provided response options:
- an = 8, 10, 12, 14, 16, ... (This does not include 6 and does not match our full sequence.)
- an = 6 + 2n (Let's check if this matches our sequence. For \( n = 1, a_1 = 6 + 2(1) = 8 \), which is incorrect.)
- an = 4 + 2n (For \( n = 1, a_1 = 4 + 2(1) = 6 \), and for \( n = 2, a_2 = 4 + 2(2) = 8 \), which matches.)
- an = 6, 4, 2, 0, -2, ... (This is a decreasing sequence and does not match.)
The correct option that represents the sequence defined by the recursion is:
an = 4 + 2n (Correct option)